2010
DOI: 10.3109/01902141003632332
|View full text |Cite
|
Sign up to set email alerts
|

Murine mechanical ventilation stimulates alveolar epithelial cell proliferation

Abstract: High tidal volume mechanical ventilation can cause inflammation and lung damage. Mechanical strain is also necessary for normal lung growth. The current work was performed to determine if mechanical ventilation with clinically utilized tidal volumes stimulates a proliferative response in the lung. Six to eight week old C57/Bl6 mice, anesthetized with ketamine/ xylozine, were ventilated for 6 hours with 10 ml/kg tidal volume, PEEP 3cm H2O. Pulmonary function testing demonstrated decreased compliance within 3 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…The presence of neutrophils in the airspace is a consistent feature of lung injury in animals and humans because these are the first cells of the immune system to be recruited to the site of inflammation [ 37 ]. In addition, we observed that MV led to recruitment of lymphocytes to the lung; our results corroborate the findings of Chess et al [ 38 ] who reported a higher percentage of lymphocytes in ventilated animals with a moderate tidal volume.…”
Section: Discussionsupporting
confidence: 92%
“…The presence of neutrophils in the airspace is a consistent feature of lung injury in animals and humans because these are the first cells of the immune system to be recruited to the site of inflammation [ 37 ]. In addition, we observed that MV led to recruitment of lymphocytes to the lung; our results corroborate the findings of Chess et al [ 38 ] who reported a higher percentage of lymphocytes in ventilated animals with a moderate tidal volume.…”
Section: Discussionsupporting
confidence: 92%
“…These differences were likely caused by variability introduced by both ventilation and smoke exposure, resulting in an interactive effect after combination of the two stimuli. Our findings after mechanical ventilation confirm those of a previous study in mice exposed to mechanical ventilation for 6 hours with 10 ml/kg tidal volume and PEEP of 3 cmH 2 O [ 42 ]. The results of that suggested that ventilation induced low-level BALF neutrophilia and proliferation of ATII cells, whereas ventilation did not increase apoptosis in ATII cells, as measured by terminal deoxynucleotidyl transferase deoxyuridine triphosphate nick-end labeling staining.…”
Section: Discussionsupporting
confidence: 91%
“…[ 16 ] Mouse studies have focused on supraphysiologic tidal volumes of 20 to 45 ml/kg to stimulate an injurious response with durations of ventilation varying from two to six hours. [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ] and lung injury has been shown to occur with short-term ventilation. However, a direct comparison between short-term and long-term ventilation in a translational model is currently lacking in the literature and it is also unknown at what time point ventilation becomes injurious.…”
Section: Introductionmentioning
confidence: 99%